1977
DOI: 10.1111/j.1365-3059.1977.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Cochliobolus sativus on Barley in Scotland

Abstract: SUMMARY Very severe infection of several crops of spring barley by Cochliobolus sativus occurred in Scotland during 1971–73. The most severely infected cultivar was Clermont, the high, susceptibility of which, combined with extensive seed infection, was responsible for the outbreak. Seed‐borne infection by C. sativus was not wholly controlled by mercurial seed treatments, although no mercury tolerance was detected. The fungus is able to overwinter in the soil in Scotland and can also survive by infecting other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This explains the observed yields in badly affected commercial crops of less than 2,500 kg/ha, when unaffected crops can yield over 6,000 to 7,500 kg/ha. WHITTLE (1977) showed that cv. Clermont was the most susceptible to C.sativus of the commonly grown barley cultivars in Scotland but it might be expected that disease severity may vary with cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains the observed yields in badly affected commercial crops of less than 2,500 kg/ha, when unaffected crops can yield over 6,000 to 7,500 kg/ha. WHITTLE (1977) showed that cv. Clermont was the most susceptible to C.sativus of the commonly grown barley cultivars in Scotland but it might be expected that disease severity may vary with cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the fungus has become more frequent in North Western Europe (JBRGENSEN 1974) and in 1971 it was isolated from all 6 crops of (RICHARDSON 1971). The further progress of the disease in Scotland is described by WHITTLE (1977) but, although the disease was associated in several cases with severe yield losses, little information exists concerning the relationship between disease severity and yield loss. Apart from a seedling blight C. sativus can cause a foot and root rot, foliar disease and head-blight.…”
Section: Introductionmentioning
confidence: 99%
“…These conidia may have been introduced to the area via seed-borne inoculum, as has recently been reported in Scotland (Whittle 1977), or may have already been present, surviving as pathogens of various grass species. They had not been introduced on seed sown in 1976, as health testing of the seed samples had shown all but one of the lines to be free of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Severe yield losses of up to 100% due to B. sorokiniana infection of wheat have been reported from sub-tropical areas (Saari, 1998). Also in temperate regions with intense barley cultivation, it has been identified as an important pathogen (Jørgensen, 1974;Whittle, 1977), with yield losses of 10-15% being reported (Stack, 1982;Kurppa, 1985;Forsberg, 2004).…”
Section: Introductionmentioning
confidence: 97%